2005
DOI: 10.1213/01.ane.0000143339.40385.1b
|View full text |Cite
|
Sign up to set email alerts
|

Positive End-Expiratory Pressure During Induction of General Anesthesia Increases Duration of Nonhypoxic Apnea in Morbidly Obese Patients

Abstract: Positive end-expiratory pressure (PEEP) applied during induction of anesthesia prevents atelectasis formation and increases the duration of nonhypoxic apnea in nonobese patients. PEEP also prevents atelectasis formation in morbidly obese patients. Because morbidly obese patients have difficult airway management more often and because arterial desaturation develops rapidly, we studied the clinical benefit of PEEP applied during anesthesia induction. Thirty morbidly obese patients were randomly allocated to one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
106
1
17

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 241 publications
(127 citation statements)
references
References 24 publications
3
106
1
17
Order By: Relevance
“…Preoxygenation in a 25°head-up position rather than in supine position before induction of anaesthesia results in a 23% higher oxygen tension, thus, allowing more time for intubation and airway control [25,26]. Similarly, positive end-expiratory pressure during induction increases the duration of non-hypoxic apnoea [27]. The volatile anaesthetic desflurane and the opioid remifentanil are recommended for maintenance of general anaesthesia since both agents have a very short half-life and are rapidly eliminated [24].…”
Section: Discussionmentioning
confidence: 99%
“…Preoxygenation in a 25°head-up position rather than in supine position before induction of anaesthesia results in a 23% higher oxygen tension, thus, allowing more time for intubation and airway control [25,26]. Similarly, positive end-expiratory pressure during induction increases the duration of non-hypoxic apnoea [27]. The volatile anaesthetic desflurane and the opioid remifentanil are recommended for maintenance of general anaesthesia since both agents have a very short half-life and are rapidly eliminated [24].…”
Section: Discussionmentioning
confidence: 99%
“…The use of 10 cm H 2 O continuous positive airway pressure/positive endexpiratory pressure (CPAP/PEEP) throughout the induction period (CPAP when breathing and PEEP after apnea) has been shown to increase the duration of apnea prior to desaturation by 50% in morbidly obese patients. 36,37 Noninvasive positive pressure ventilation using pressure support ventilation with PEEP via a face mask has also been shown to enhance preoxygenation, achieving a more rapid increase and higher end-tidal O 2 when compared with preoxygenation with spontaneous ventilation. 38 …”
Section: Positioning and Preoxygenationmentioning
confidence: 99%
“…Il a été démontré que le recours à une ventilation en pression positive continue / pression positive télé-expiratoire de 10 cm H 2 O (CPAP / PEEP) tout au long de la période d'induction (CPAP lors de la respiration et PEEP après l'apnée) augmentait la durée de l'apnée avant désaturation de 50 % chez les patients obèses morbides. 36,37 En outre, il a également été démontré que la ventilation en pression positive non effractive utilisant une aide inspiratoire et une PEEP via un masque facial améliorait la préoxygénation, résultant en une augmentation plus rapide et un O 2 télé-expiratoire plus élevé comparativement à une préoxygénation en ventilation spontanée. 38 …”
Section: Positionnement Et Préoxygénationunclassified
“…Important limitations of this study were the absence of ventilation between the onset of apnea and intubation, and the relative brevity of the pre-oxygenation (only 3 minutes). Later studies, however, showed a benefi t of applying CPAP with oxygen during pre-oxygenation in morbidly obese patients [18], [19]. Compared to O 2 alone, CPAP of 10 cmH 2 O + O 2 for 5 min increased the time to desaturate and reduced the amount of atelectasis following intubation [18], [19].…”
Section: Non-invasive Ventilation With Positive Pressurementioning
confidence: 99%
“…Later studies, however, showed a benefi t of applying CPAP with oxygen during pre-oxygenation in morbidly obese patients [18], [19]. Compared to O 2 alone, CPAP of 10 cmH 2 O + O 2 for 5 min increased the time to desaturate and reduced the amount of atelectasis following intubation [18], [19]. Immediately after intubation, the amount of atelectasis measured by computed tomography (CT) was 10 % in the oxygen group compared to only 2 % in the 10 cmH 2 O PEEP group [18].…”
Section: Non-invasive Ventilation With Positive Pressurementioning
confidence: 99%